2017
DOI: 10.1002/adma.201703702
|View full text |Cite
|
Sign up to set email alerts
|

A Eutectic Mixture of Natural Fatty Acids Can Serve as the Gating Material for Near‐Infrared‐Triggered Drug Release

Abstract: A smart release system responsive to near-infrared (NIR) light has been developed for intracellular drug delivery. We demonstrate the concept by co-encapsulating doxorubicin (DOX, an anticancer drug) and IR780 iodide (IR780, a NIR-absorbing dye) into nanoparticles made of a eutectic mixture of naturally occurring fatty acids. The eutectic mixture has a well-defined melting point at 39 °C, which can be used as a biocompatible phase-change material for NIR-triggered drug release. The resultant nanoparticles exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
147
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 179 publications
(155 citation statements)
references
References 48 publications
0
147
0
Order By: Relevance
“…In a follow-up study, we further demonstrated the fabrication of phase-change nanoparticles based on the same eutectic mixture and achieved NIR-triggered intracellular drug release. 50 It is worth pointing out that in both studies, the use of a mixture of fatty acids was able to substantially increase the drug loading capacity because of the decreased crystallinity for the matrix upon solidification.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 91%
“…In a follow-up study, we further demonstrated the fabrication of phase-change nanoparticles based on the same eutectic mixture and achieved NIR-triggered intracellular drug release. 50 It is worth pointing out that in both studies, the use of a mixture of fatty acids was able to substantially increase the drug loading capacity because of the decreased crystallinity for the matrix upon solidification.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 91%
“…[96] Accordingly, efficient NIR-responsive drug delivery vehicles attracted immense interest. [98] In addition, the hollow structures required less energy for heat stress and thermo-induced deformations, which might offer supersensitive drug release for enhanced drug availability and biosafety. [97] Compared with solid ones, hollow particles, with multicompartment architectures, enabled the rational co-encapsulations of multiple bioactive substances and NIR-sensitive molecules (e.g., IR780, integrating indocyanine green, porphyrin, and dopamine).…”
Section: Photothermic-sensitive Deliverymentioning
confidence: 99%
“…[97] Compared with solid ones, hollow particles, with multicompartment architectures, enabled the rational co-encapsulations of multiple bioactive substances and NIR-sensitive molecules (e.g., IR780, integrating indocyanine green, porphyrin, and dopamine). [98] In addition, the hollow structures required less energy for heat stress and thermo-induced deformations, which might offer supersensitive drug release for enhanced drug availability and biosafety. [99] In a recent study, spindle-like polypyrrole hollow nanocapsules were employed for NIR-sensitive DOX Adv.…”
Section: Photothermic-sensitive Deliverymentioning
confidence: 99%
“…[24] In ac ompletely different application, fatty acids have been explored as anew class of gating materials for controlled release by leveraging their welldefined, sharp melting points. [25][26][27][28][29] In principle,s olid microparticles of fatty acids can be used as am ulti-functional platform to present topographic guidance while offering achemical cue and serving as agating material for controlled release.…”
mentioning
confidence: 99%
“…Herein, we utilized electrospray to fabricate solid microparticles from amixture of lauric acid and stearic acid, which was formulated with asharp melting point at 39 8 8Ctoensure structural integrity when cultured with cells. [25][26][27] We varied the densities of the microparticles on glass slides to construct substrates with controllable topographical cues to optimize the outgrowth of neurites from PC12 cells.W ealso examined the influences of the microparticles on neurite outgrowth by benchmarking against free fatty acids at different concentrations.F urthermore,w ed eposited the microparticles on uniaxially aligned, electrospun microfibers at an optimal density to direct the outgrowth of neurites from both PC12 multicellular spheroids and chick embryonic dorsal root ganglia (DRG) bodies.…”
mentioning
confidence: 99%